2016
DOI: 10.1586/14737140.2016.1129903
|View full text |Cite
|
Sign up to set email alerts
|

Dose-related efficacy and toxicity of gemtuzumab ozogamicin in pediatric acute myeloid leukemia

Abstract: Gemtuzumab ozogamicin, an anti-tumour antibiotic linked to an anti-CD33 antibody (Mylotarg®), has been well studied in AML in adults but to a lesser extent in children. No review has yet been published on the dose-related toxicity and efficacy of gemtuzumab ozogamicin in pediatric AML patients. Here we looked at 14 studies then scatterplots and linear regressions were used to estimate the relationship between the dose of gemtuzumab and its toxicity and efficacy. A nonsignificant increase in bilirubin level and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…In children, GO has been used in non‐APL AML with encouraging results, as recently reviewed by Parigger et al (). Further, GO induced a sustained molecular CR in combination with ATO in a child with multiply relapsed APL (Inoue et al , ).…”
Section: Treatment Of Relapsed Aplmentioning
confidence: 97%
“…In children, GO has been used in non‐APL AML with encouraging results, as recently reviewed by Parigger et al (). Further, GO induced a sustained molecular CR in combination with ATO in a child with multiply relapsed APL (Inoue et al , ).…”
Section: Treatment Of Relapsed Aplmentioning
confidence: 97%
“…However, SOS has also been reported in less than 1% of children not treated with GO-containing chemotherapy (Gamis et al, 2014). The risk of GO-induced SOS seems related to the dose of GO (Parigger et al, 2016). In children with newly diagnosed AML treated with chemotherapy plus GO at 3 mg/m 2 , SOS of any degree of severity was observed in less than 4%.…”
Section: Sinusoidal Obstruction Syndromementioning
confidence: 99%
“…The efficacy of gemtuzumab ozogamicin is promising, but so far has not replaced the intensive use of anthracyclines (Parigger et al, 2016) but may give a survival benefit when added to conventional chemotherapy (Hills et al, 2014). Protocols without the anthracycline-cytarabine based induction, a combination that results in major side effects, have not been successful.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, results of an analysis indicated that higher doses of GO account for more adverse events. 65 …”
Section: Immunotherapymentioning
confidence: 99%